Population, Virulence, and Mycotoxin Profile of Fusarium spp. Associated With Basal Rot of Allium spp. in Vietnam - Lê, Dũng (The American Phytopathological Society (APS), 2023)
Fusarium basal rot (FBR) is particularly problematic to Allium producers worldwide. In Vietnam, information on the profile of FBR is scarce, even though the presence of Fusarium spp. in Allium plants has long been recorded. In this study, a total of 180 isolates of Fusarium spp. were recovered from Allium bulbs/plants showing symptoms of FBR in 34 commercial Allium fields around Da Lat, Lam Dong, Vietnam. These isolates were identified to the species level by sequencing the internal transcribed spacer region and the translation elongation factor 1α gene. F. oxysporum was most prevalent (81%) in samples from all locations and Allium varieties, followed by F. solani (15%) and F. proliferatum (4%), which were only found in onion (Allium cepa L.). Pathogenicity tests on onion seedlings (56 isolates) and mini bulbs (10 isolates) indicated that onion can be infected by all of these species but virulence varied greatly between isolates. Moreover, isolates that were virulent on seedlings were sometimes not virulent on bulbs and vice versa, which points to a specialization of isolates for the host phenology. Mycotoxin analyses showed that the highest amounts of beauvericin were detected in seedlings and bulbs infected by F. oxysporum, whereas F. proliferatum was mainly responsible for the presence of fumonisin B1 in bulbs, suggesting a natural occurrence of beauvericin and fumonisin B1 in onions infected by these pathogens.